Manajemen Pendidikan Karakter Melalui Apel Online Untuk Memotivasi Belajar Siswa Pada Masa Pandemi Covid-19 - Iis Kurniasih; Sofyan Sauri; Wiwik Dyah Aryani (Peneliti.net, 2022)
The purpose of this study is to describe the planning, implementation, evaluation, barriers and challenges of character education through online apples to motivate student learning during the covid-19 pandemic. This type of research uses a qualitative case research method that describes the experience of an intensive situation. Sources of research data are school principals, PAI teachers to parents. The object of this research is to motivate the learning of Smart Global Skills Vocational High School students in Bandung. Collecting data by observation, interviews, documentation and triangulation. The data analysis technique uses the Miles and Huberman model with steps; streamlining data, presenting data, drawing conclusions. The results of this study are: (1) Planning for character education through online apples to motivate student learning during the Covid-19 pandemic first identify and analyze character education problems, formulate goals for online apple activities, make schedules at the beginning of lessons and arrange online apple officers and religious programs, develop assessment instruments, and communicate with parents. (2) Character education through online apples during the research was carried out well by going through the stages; the teacher communicates things that are prepared by students in online learning, informs the schedule and divides online apple assignments in turns, carries out online apples, the teacher motivates with praise. (3) Evaluation is carried out during the online apple ceremony through attendance, discipline, cooperation, and maintaining the online apple situation through an assessment rubric. (4) Obstacles during online apples include; Internet access is not stable, parents do not accompany learning, students feel bored and bored. The solution is that teachers are required to master creative and innovative technology, provide internet and study quotas, and respond quickly to learning difficulties.